2012
DOI: 10.1038/modpathol.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papilloma virus and p16 expression in high-grade adenoid cystic carcinoma of the head and neck

Abstract: Squamous cell carcinoma of the head and neck, particularly basaloid squamous cell carcinoma, may be difficult to distinguish from high-grade adenoid cystic carcinoma. Evidence of human papilloma virus (HPV) infection, particularly HPV 16, is frequently found in non-keratinizing oropharyngeal squamous cell carcinoma. Immunoreactivity for p16, a surrogate marker for HPV infection, often parallels the HPV infection status in oropharyngeal squamous cell carcinoma. However, the incidence and correlation between p16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 22 publications
(28 reference statements)
2
83
0
1
Order By: Relevance
“…therapeutic vaccines and de-intensification therapy). Recent studies have suggested that, like the oropharynx, the salivary glands may also be targeted by oncogenic HPV [13,[16][17][18]. These HPV-related forms of salivary gland cancer warrant considerable attention as they could provide new insights into a type of head and neck cancer in which little is known about the biologic mechanisms underlying tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…therapeutic vaccines and de-intensification therapy). Recent studies have suggested that, like the oropharynx, the salivary glands may also be targeted by oncogenic HPV [13,[16][17][18]. These HPV-related forms of salivary gland cancer warrant considerable attention as they could provide new insights into a type of head and neck cancer in which little is known about the biologic mechanisms underlying tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In light of potential clinical repercussions, claims regarding the identification of a new form of HPV-related head and neck cancer warrant careful corroboration. For example, the existence of a newly identified HPV-related adenoid cystic carcinoma either has been unconfirmed in subsequent studies or has been redefined as non-salivary gland carcinoma [5,16,19,20]. Recently, Isayeva et al [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Boland et al [28] investigated the expression of p16 expression and the presence of HPV in adenoid cystic carcinoma of different head and neck sites. Using ISH for high-risk HPV, the authors found that only 2 of 25 (8 %) cases were positive for HPV.…”
Section: Discussionmentioning
confidence: 99%